Elements Affecting Seed Potato Quality In India- A Review - Sadawarti, Murlidhar J.; Singh, S. P.; Buckseth, Tanuja; Devi, Sugani; Singh, R. K.; Kumar, Vinod; Katare, Subhash; Singh, Brajesh; Khambalkar, Priyadarshani A.; Samadhiya, R. K.; et al. (International Journal of Bio-resource and Stress Management, 2023)
Potato has high potential for food and nutritional security. In India, potato cultivation was spread over different states over diverse agro-climatic conditions. Even though edaphic and climatic conditions are suitable for cultivation in India, national average productivity is very low (24.12 t ha-1) as compared to some of the developed countries in the world. Hence with increasing demand of potato, high quality seed is of utmost importance to increasing the productivity. Quality seed is a critical input in potato cultivation and accounts for about 40–50% of the total cost of cultivation. Most significant constraint in lower productivity is attributed to lack of quality seed tubers especially to small and marginal farmers in India. Varietal purity, seed health, physiological age, prevalence of pest and diseases, change in virus vector relationship and poor knowledge of seed selection and ignorance about Seed Plot Technique are the important aspects which affect the seed potato quality. Pre harvest and post-harvest elements viz selection of variety, area of seed production/climatic conditions, agronomy/ agro techniques for seed production, improving tuber size, rouging, plant protection measures, harvesting, post harvest handling and storage are the important elements which affect quality of seed potato production. Therefore, this review mainly focuses on the above said factors for the quality seed potato production and further enhancement of the productivity.